2022
DOI: 10.1108/prt-02-2022-0024
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable exploration of coffee extracts (coffea arabica l.) for dyeing of microwave-treated bio-mordanted cotton fabric

Abstract: Purpose This study aims to observe the coloring efficacy of coffee-based natural brown colorant for cotton dyeing under microwave (MW) treatment. Design/methodology/approach The colorant extracted in particular (neutral and acidic) media was stimulated by MW treatment up to 6 min. Dyeing variables were optimized and 2–10 g/100 mL of sustainable anchors (mordants) have been used to get colorfast shades. Findings It has been found that un-irradiated acidic extract (RE) containing 5% of table salt at 80 °C fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Secondary metabolites of the plant extracts are used as tonic and herbal system that transfers their biological activities when employed on matrices such as silk, wool, and cotton [9,10]. The most vital factor is that the cultural heritage with a broad spectrum of colours is now being revived as state-ofthe-art for the colouration of different substrates [11,12]. Besides the advantages of natural dyes, these have limitations, such as poor colour yield, low fastness rating, reproducibility of shades, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary metabolites of the plant extracts are used as tonic and herbal system that transfers their biological activities when employed on matrices such as silk, wool, and cotton [9,10]. The most vital factor is that the cultural heritage with a broad spectrum of colours is now being revived as state-ofthe-art for the colouration of different substrates [11,12]. Besides the advantages of natural dyes, these have limitations, such as poor colour yield, low fastness rating, reproducibility of shades, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine, chlorogenic acid, polyphenols, flavonoids, alkaloids, and other phytochemicals are the important ones, while polyphenol (chlorogenic acid) is the main functional moiety. Adeel et al ( 2023d ) dyed cotton in a microwave environment with the dye obtained from coffee beans and using bio-mordants obtained from turmeric and pomegranate peel extracts. It has been stated that reddish-yellow tones can be obtained from dyeing, depending on the MW rate and bio-mordant.…”
Section: Mordant Agentsmentioning
confidence: 99%
“…T. citrina ), could be a natural procedure for the production of green Iranian carpet. Adeel et al [ 128 ], on the other hand, claimed that the natural dye obtained from coffee can have a good impact on the ecosystem and global society, since it is not carcinogenic. Moreover, Samant et al [ 129 ] reported that dyed fabric obtained from Acacia catechu showed antibacterial activities against E. coli and S. aureus .…”
Section: Application Of Natural Antimicrobialsmentioning
confidence: 99%